No country for old men [videorecording (DVD)] - Coen, Ethan; Coen, Ethan; Coen, Ethan; Coen, Joel; Coen, Joel; Coen, Joel; Jones, Tommy Lee, 1946-; Bardem, Javier, 1969-; Brolin, Josh; McCarthy, Cormac, 1933- (Paramount, 2020)
A man living in a small Texas town comes across a crime scene and finds two million dollars, and a killer is set on his trail to recover the money.